2018
DOI: 10.3389/fphar.2018.00462
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-neuroinflammatory Activity of Tectorigenin Pretreatment via Downregulated NF-κB and ERK/JNK Pathways in BV-2 Microglial and Microglia Inactivation in Mice With Lipopolysaccharide

Abstract: The activation of microglia is decisively involved with the neurodegeneration observed in many neuroinflammatory pathologies, such as multiple sclerosis, Parkinson’s disease, and Alzheimer’s disease. Tectorigenin (TEC) is an isoflavone isolated from various medicinal plants, such as Pueraria thunbergiana Benth, Belamcanda chinensis, and Iris unguicularis. In the present study, the neuroinflammatory effects of TEC were evaluated in both lipopolysaccharide (LPS)-treated BV-2 microglial and mouse models. TEC rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 38 publications
4
61
0
Order By: Relevance
“…Previously, Xia et al [ 40 ] found that MPTP induced apoptotic cell death through Bax and caspase-3. Recently, it has also been reported that the expression level of cytochrome C is upregulated by MPTP intoxication [ 41 ]. Similarly, PARP-1 is reportedly cleaved after MPTP treatment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Xia et al [ 40 ] found that MPTP induced apoptotic cell death through Bax and caspase-3. Recently, it has also been reported that the expression level of cytochrome C is upregulated by MPTP intoxication [ 41 ]. Similarly, PARP-1 is reportedly cleaved after MPTP treatment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…To find out the signal pathways that are responsible for the effect of LRCH1, we analyzed the MAPK pathways because they are critical to LPS-mediated pro-inflammatory activation of microglia [26,27]. As shown in Figure 5 and Supplementary figure 4, under unprimed condition, the activating phosphorylation of p38 MAPK, Erk1/2, and JNK was comparable in LC-infected microglia and LL-infected microglia.…”
Section: Lrch1 Knockdown Promotes the Activation Of P38 Mapk And Erk1/2mentioning
confidence: 99%
“…Activation of ERK by phosphorylation is a key step in regulation of microglial pro-inflammatory phenotype [33,34], and is known to play a role in microglial pro-inflammatory processes in a Parkinson's disease mouse model [35,36]. We hypothesized that this pathway might be involved in promotion of the anti-inflammatory phenotype by monomeric α-Syn.…”
Section: Monomeric α-Syn May Regulate Microglia Towards Anti-inflammamentioning
confidence: 99%
“…The pro-inflammatory, neurotoxic effects of activated microglia are implicated in neuronal cell death in Parkinson's disease [14,34,41,42]. Therefore, we also investigated whether modulating of microglia toward an anti-inflammatory phenotype by monomeric α-Syn would have neuroprotective effects in an in vivo mouse model of synucleinopathy.…”
Section: Mptpmentioning
confidence: 99%